Finding the Truth in A Virtual Courtroom: Criminal Trials in Indonesia during the COVID-19 - Febby Mutiara Nelson; Intan Hendrawati; Rafiqa Qurrata A’yun (Faculty of Law, Sriwijaya University, Indonesia, 2023)
Video conferencing through video call platforms, such as Zoom and Google Meet, has become a useful option for judges holding criminal trials during the COVID-19 pandemic in many countries. This trend also occurred in Indonesia. Some judges believe that video conferencing technology will help them accomplish justice in an emergency, referring to the legal maxim 'salus populi suprema lex esto’ or ‘let the welfare of the people be the supreme law’. Although virtual trials assist courts in preventing the spread of the deadly virus, they have also affected the work of judges to reach the substantive truth. This paper examines the challenges concerning the rights of the accused and technological matters that have emerged under the use of virtual courtrooms and, in some ways, led to unfair trial procedures. We argue that the absence of laws that regulate virtual courtrooms, along with an outdated the Code of Criminal Procedure in Indonesia (KUHAP), can lead to miscarriages of justice. The arguments presented in this article are based on survey data conducted from December 2020 to January 2021. The respondents are judges from Indonesia's western, middle, and eastern regions who used video conference facilities for criminal court hearings during the COVID-19 outbreak of 2020-2021.